2023
DOI: 10.11591/eei.v12i1.4028
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of linear model on stunting prevalence with machine learning approach

Abstract: An increase in the number of residents should be anticipated including in the health sector, especially the problem of stunting. Stunting in children disrupts height and lack of absorption of nutrients. Information and data drive change in many areas such as health, entertainment, economics, business, and other strategic areas. The stages carried out in this study are initiating, developing linear models, and making prediction results on linear machine learning models. The results of testing with the scikit-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Teknik ini melibatkan penggunaan algoritma dan model statistik untuk mengidentifikasi pola dalam data dan membuat prediksi atau keputusan tanpa instruksi yang eksplisit. Implementasi ML telah banyak di terapkan untuk melakukan prediksi dalam berbagai kasus [13], [14]. Pada kasus stunting, beberapa metode ML yang telah digunaakan adalah metode DT [15], Naïve Bayes [16], [17], SVM [18], k-Nearest Neighbors [19], Neural Networks [20], [21], Random Forest [22], [23] dan Logistic Regression [24] [25].…”
Section: Machine Learning (Ml)unclassified
“…Teknik ini melibatkan penggunaan algoritma dan model statistik untuk mengidentifikasi pola dalam data dan membuat prediksi atau keputusan tanpa instruksi yang eksplisit. Implementasi ML telah banyak di terapkan untuk melakukan prediksi dalam berbagai kasus [13], [14]. Pada kasus stunting, beberapa metode ML yang telah digunaakan adalah metode DT [15], Naïve Bayes [16], [17], SVM [18], k-Nearest Neighbors [19], Neural Networks [20], [21], Random Forest [22], [23] dan Logistic Regression [24] [25].…”
Section: Machine Learning (Ml)unclassified
“…Regression is a method of estimating relationships from given data to describe the characteristic of a data set [27]. This relationship can then be used for various calculations such as for forecasting future values [28]. In polynomial regression, the correlation between the explanatory and response variables is represented by a polynomial of the appropriate degree.…”
Section: Polynomial Regressionmentioning
confidence: 99%
“…Furthermore, Febrina et al identified nutritional factors such as low birth weight in infants, chronic energy deficiency in pregnant women, and insufficient complementary feeding alongside breastfeeding as contributors to stunting [11]. Meanwhile, studies on environmental factors such as sanitation and clean water access have produced differing conclusions [12,13]. Drawing on these insights, this study investigates the roles of social, governmental, nutritional, and environmental factors in stunting prevalence within districts and cities by utilising a wide array of variables.…”
Section: Literature Reviewmentioning
confidence: 99%